2017
DOI: 10.1080/02670844.2016.1201366
|View full text |Cite
|
Sign up to set email alerts
|

Crack healing in Y-doped Cr2AlC-MAX phase coatings

Abstract: Self-healing materials facilitate a design concept which includes damage management, where damage that is inflicted during operation can be healed autonomously. It has been shown that the M n+1 AX n phases Ti 3 AlC 2 , Ti 2 AlC and Cr 2 AlC exhibit such behaviour. Cracks are filled and hence healed by oxidation products of the M and A elements in the MAX phase at the high operating temperatures in which they are used. After crack healing the fracture strength is recovered to the level of the virgin material. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…Berger and Boucher [103] reported that the addition of yttrium (Y) is one of the ways to promote the growth of Al 2 O 3 in Cr 2 AlC. Y-containing Cr 2 AlC coating exhibits an excellent self-healing ability to repair microcracks of 43 μm in length and 200 nm in width at 900 for ℃ 1 h in air [103]. To further improve the healing efficiency of MAX phases, controlling the crack-filling phases with chemical stability and mechanical match to the MAX phases and promoting growth of such filling phases is necessary to consider.…”
Section: Crack Healing In Airmentioning
confidence: 99%
See 2 more Smart Citations
“…Berger and Boucher [103] reported that the addition of yttrium (Y) is one of the ways to promote the growth of Al 2 O 3 in Cr 2 AlC. Y-containing Cr 2 AlC coating exhibits an excellent self-healing ability to repair microcracks of 43 μm in length and 200 nm in width at 900 for ℃ 1 h in air [103]. To further improve the healing efficiency of MAX phases, controlling the crack-filling phases with chemical stability and mechanical match to the MAX phases and promoting growth of such filling phases is necessary to consider.…”
Section: Crack Healing In Airmentioning
confidence: 99%
“…Therefore, promotion of the rapid growth of Al 2 O 3 should be considered in the crack healing of MAX materials. Berger and Boucher [103] reported that the addition of yttrium (Y) is one of the ways to promote the growth of Al 2 O 3 in Cr 2 AlC. Y-containing Cr 2 AlC coating exhibits an excellent self-healing ability to repair microcracks of 43 μm in length and 200 nm in width at 900 for ℃ 1 h in air [103].…”
Section: Crack Healing In Airmentioning
confidence: 99%
See 1 more Smart Citation
“…The crack in the MAX-phase coatings fills with oxide of predominantly alumina to form a covering protection layer on the crack flanks. [13] The successful synthesis of these thin films by the utilization of several coating techniques, e.g., magnetron sputtering or plasma spraying and the application as protective layers for metallic high temperature alloys has been published in numerous previous work. [8,[14][15][16][17] The alumina forming MAX-phases are in particularly promising as protective coatings for γ-TiAl-based titanium aluminide alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Cr 2 AlC presents a density of 5.23 g/cm 3 , high Young's modulus (288 GPa), intermediate fracture toughness (5.2 MPa √ m), good flexural (354 MPa) and compression strengths (1160 MPa) [3,4,12]. Furthermore, bulk Cr 2 AlC materials are good electrical and thermal conductors, show excellent oxidation resistance at high temperature in air and exhibit self-healing mechanisms at high temperature [13][14][15]. However, their high-temperature mechanical properties are largely unknown, and the mechanism responsible for the oxidation resistance is not fully understood.…”
Section: Introductionmentioning
confidence: 99%